Efforts to Improve the Health Status of Junior High School Students Through the Development of School Health Programs (Indian Journal of Public Health Research & Development, 2020)
One form of health promotion for school students is the school health program in every region in Indonesia.The purpose of School Health according to the Ministry of Education and Culture in 2012 is to improvethe quality of education and student achievement by improving the quality of clean and healthy life andhealth status of students and creating a healthy environment. This research was conducted using qualitativedescriptive method with the aim of developing a model of implementing school health programs. Respondentsin this study were students from junior high schools managed by the government and junior high schoolsmanaged by private parties implementing school health programs. The results of this study are expectedto support existing models by improving school health management through a systems approach so thatstudents can improve their performance through improving clean and healthy living behaviors and a healthyenvironment
Keywords: Health promotion, health school, development, junior high schools, systems approach